Self and proxy (parents and teachers') reports of child motor competence: A three-year longitudinal study. (January 2023) - Estevan, Isaac; Bowe, Steven J.; Menescardi, Cristina; Barnett, Lisa M.
Abstract: Objective: The aims of this study were to: 1) analyse the longitudinal trends in the evolution of the association between children's actual and perceived motor competence (AMC and PMC, respectively) according to the source of information: children, parents, and Physical Education (PE) teachers; 2) assess whether children, parents, and PE teachers can report on children's AMC longitudinally (considering the children's age, sex, and the type of motor competence). Design and method: A sample of 108 typically developing Spanish children (47.12% girls) from five schools participated in this study. AMC and PMC (locomotion, object control and overall MC) data was collected at three time points one year apart. Longitudinal mixed effects models with repeated measures were conducted. Results: Regardless of the domain of MC, no longitudinal association between children's AMC and PMC was found. Parents also exhibited limited capability to proxy report their children's AMC longitudinally. PE teachers' proxy reports of children' AMC were associated over time with object control and overall level. Conclusion: This study confirms the necessity of specific training in AMC to effectively report on children's motor competence. PE teachers can be seen as a potential source to empower children's AMC and PMC development over time. Highlights: Children's actual motor competence (MC) increases as a function of age but this is not the case for their perceived MC. Physical Education teachers are able to report on children's motor competence over time. Neither children or parents appear to be able to report on children's motor competence over time.